Analysis of the impact of the new revenue recognition guidance in US GAAP on a consulting company - Salihbegovic, Amna (2018)
The aim of this master thesis is to examine the new revenue recognition guidance in US GAAP, ASC 606 – Revenue from contracts with customer in the context of management and IT consulting company. Theoretical part of the thesis contains description of old guidance with emphasis on software arrangements. Detailed analysis of the new regulation stated in the ASC 606 is also provided as well as 5-step model. This analysis also includes recognition of revenue from license of intellectual property. Practical part of the thesis focuses on the analysis of current accounting policies of a consulting company in the context of the new standard. New revenue recognition principles are applied on several examples of consulting and outsourcing contracts and outlined are the changes that will need to be implemented by the company.